Accumulation of amadori and maillard products in wheat seeds aged under different storage conditions - Strelec, Ivica (Array, 2008)
Summary: Occurrence of protein modification by Amadori and Maillard reactions in wheat seeds during ageing at different temperatures and relative humidities (RH) has been investigated over 12 month period. Spectrofluorimetric determination of Maillard products of partially purified proteins extracted from aged seeds revealed increase of protein fluorescence at 325/425 nm (excitation/emission wavelength). The highest increase of Maillard products was observed for seeds aged at 40 °C, RH = 45 %, followed by storage at 25 °C, RH = 45 % and storage at warehouse conditions (10–30 °C, RH = 40–70 %), while seeds kept at 4 °C, RH = 40 % did not show significant accumulation of Maillard products. Similar pattern of accumulation were observed for Amadori products, except for seeds aged at 40 °C, RH = 45 %, where products decreased after 270 days of storage. Obtained data indicate that a wheat seed ageing during storage is associated with protein modification by Amadori and Maillard reactions. However, the contribution of these reactions varies under different storage conditions